Why Being a Periphery is not Honorable, and why It does not Threaten Russia - N. M. Mezhevich (Управленческое консультирование, 2020)
The foreign policy of theRussian Federationattracts the attention of experts and researchers not only during the days of obvious victories, but also during periods of serious trials.Russiamanaged not to become the periphery of any Center; this is the fi st, necessary, but not the only condition forNationalStatedevelopment. The second condition is the formation of such a foreign policy, which does not focus on cooperation with any exclusive partner, but clearly and unequivocally declares:Russiaitself is the center of power.